Advances in the understanding and enhancement of the human cognitive functions of learning and memory. Issue 4 (December 2022) - Amoah, Daniel Kofi
Learning and memory are among the key cognitive functions that drive the human experience. As such, any defective condition associated with these cognitive domains could affect our navigation through everyday life. For years, researchers have been working toward having a clear understanding of how learning and memory work, as well as ways to improve them. Many advances have been made, as well as some challenges that have also been faced in the process. That notwithstanding, there are prospects with regards to the frontier of the enhancement of learning and memory in humans. This review article selectively highlights four broad areas of focus in research into the understanding and enhancement of learning and memory. Brain stimulation, effects of sleep, effects of stress and emotion, and synaptic plasticity are the main focal areas of this review, in terms of some pivotal research works, findings and theories.